2012
DOI: 10.1016/j.aop.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite entanglement in systems of identical particles: The partial transposition criterion

Abstract: We study bipartite entanglement in systems of N identical bosons distributed in M different modes. For such systems, a definition of separability not related to any a priori Hilbert space tensor product structure is needed and can be given in terms of commuting subalgebras of observables. Using this generalized notion of separability, we classify the states for which partial transposition turns out to be a necessary and sufficient condition for entanglement detection.1 See [1] and references therein.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
147
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(148 citation statements)
references
References 67 publications
1
147
0
Order By: Relevance
“…But, as a closer look at the literature on the subject [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] reveals, it is apparent that there is no consensus yet as to what the proper formalism should be.…”
Section: Introductionmentioning
confidence: 99%
“…But, as a closer look at the literature on the subject [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] reveals, it is apparent that there is no consensus yet as to what the proper formalism should be.…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly shown that the entanglement measure defined in terms of the normalized von Neumann entropy of the reduced density matrix of the atoms reaches its maximum value at the critical point of the QPT, when the system is most chaotic. When a quantum many-body system undergoes a QPT, there is always a noticeable change in many ground state quantities, such as particle number statistics and the entanglement measure at the critical point [35][36][37]. However, it is not necessarily true that the system is most entangled at the critical point.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a noticeable change in the ground state Shannon information entropy near or at the critical point can also be observed when j is large. Anyway, the above analysis justifies the connection of particle number statistics with entanglement observed in [35][36][37]. …”
Section: The Qpt and Entanglementmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of quantum correlations with identical particles cannot rely on the tensor product structure of single particle Hilbert spaces, but must be reformulated in terms of subsets of locally manipulable observables [23,24,25,26,16,27,28]. This powerful approach generalizes the theory of entanglement of distinguishable particles.…”
mentioning
confidence: 99%